An interdisciplinary approach to evaluation of the results of dental implantation and prosthetic treatment - A.Yu. Kordiyak; A.M. Bordovskyi; M.I. Servetnyk; R.T. Hryvul (Acta Medica Leopoliensia, 2018)
Аim of the present study is to set up a procedure for interdisciplinary interaction in complicated orthopaedic cases with the analysis of causes of complications after dental implantation and prosthetic treatment.